Analisis pengaruh desain kerja terhadap knowledge productivity arsiparis di Arsip Nasional Republik Indonesia - Ursa Agniya; Tamara Adriani Salim (Berkala Ilmu Perpustakaan dan Informasi, 2023)
Introduction. This study discusses how a job design influences knowledge productivity among archivists at the Indonesian National Archives. A job design is examined with knowledge productivity and the relationship between them. The three job design was used to measure knowledge productivity characteristics (motivation, social, and work context). Data Collection Methods. This research used a quantitative approach with qestionnaires distributed in March-April 2021 to archivists at The National Archives of Indonesia Data Analysis. The validity and reliability of the instrument were processed using the IBM SPSS v26 program. Results and Discussion. The results showed that the job design had a relationship with knowledge productivity of 0.859 with a significance value (Sig.) of 0.000 and a coefficient of determination of 0.738. The results of the regression analysis showed Y = 37.707 + 0.189X means that job design has a positive effect on knowledge productivity. Conclusion. Based on data analysis, there is a positive influence between job design and knowledge productivity. It was found that knowledge productivity variable that the work context indicator did not have a significant effect on knowledge productivity.